Genetic characterization of selected Nile tilapia in Santa Catarina - Silva, Bruno Corrêa da; Pereira, Adriana; Massago, Haluko; Mariguele, Keny Henrique (Semina: Ciências Agrárias, 2020)
Different Nile tilapia stocks belonging to the fish breeding program of the Epagri (Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina) were characterized by microsatellite markers. A total of nine stocks (S1 to S9) were evaluated, and for each stock the caudal fin of 30 individuals were sampled. A total of 75 alleles were found at the 11 microsatellite loci used (UNH104, UNH108, UNH160, UNH208, UNH222, UNH848, UNH879, UNH898, UNH952, UNH998). Among the loci used, only UHN160 showed significance for null alleles in stocks S1, S2, S3 and S5. The average number of alleles per loci was 6.8, while the average number of alleles per tilapia stock was 4.4. Five unique alleles were identified between the stock S1 and S5. The observed heterozygosity values (Ho) exceeded the expected heterozygosity (He), resulting in a negative inbreeding coefficient (FIS = -0.092). FST for the total population was 0.109, demonstrating moderate genetic differentiation between the stocks. According to the Euclidean distance, three groups were formed as follows: I - S6, S7 and S9; II - S2, S3 and S4; and III - S1, S5 and S8. However, the existence of two groups can be observed from the PCoA representation: I - S6, S7, S8 and S9; and II - S1, S2, S3, S4 and S5. The formation of these two genetic groups is consistent with the genealogy of stocks. The formation of group III (S1, S5 and S8) in the dendrogram can be explained by the higher average observed heterozygosity values of these stocks. Bayesian analysis revealed the formation of 16 groups with an FST value of 0.2107. This result reinforces the existence of variability existing in the Epagri breeding program, from which it is possible to form heterotic groups to enable the direction of potential crosses to obtain genetic gain. The study enabled genotypic characterization of the tilapia brood stock used in the Epagri breeding program, determining the genetic distance between the stocks, which will enable more accurate selection of individuals for mating for the next generation. It was possible to verify that there is high heterozygosity within the stocks, and moderate genetic differentiation between the stocks. Furthermore, all evaluated markers were polymorphic for this brood stock and will be used to characterize the next generations.